IL-9 receptor: Regulatory role on FLS and pannus formation. (November 2018) - Raychaudhuri, Smriti K.; Abria, Christine; Maverakis, Emanual Michael; Raychaudhuri, Siba P.
Abstract: Objective: Functions of the Th9 cells and its signature cytokine IL-9 in human autoimmune diseases is currently under extensive research. Here we are reporting new functions of IL-9-receptor (IL-9R); its regulatory role on (i) FLS (fibroblast like synoviocyte) biology and (ii) pannus formation in rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Methods: RA, PsA, and OA synovial tissue biopsies were obtained; FLS were derived and cultured from these tissues. T quantify protein and messenger RNA levels of IL9-receptor (IL-9R) Western blot and real-time PCR techniques were used. For Pro-growth/survival effect of IL-9 (rIL-9) Annexin-V (apoptosis assay) and MTT assays were used. Results: Immunoblot and RT-PCR studies demonstrated IL9-R in FLS of RA, PsA, and OA. IL9-R was functionally active. rIL-9 induced significant proliferation of FLS (p < 0.001) and had an inhibitory effect on TNF-α induced apoptosis. Proliferation of FLS induced by rIL-9 could be significantly inhibited (p < 0.001) with an IL-9R antibody. Further we observed, rIL-9 induced increased secretion of IL-6, IL-8 and also unregulated MMP-3 expression in FLS. Conclusions: Proliferation of FLS, induction of pro-nflammatory cytokines and upregulation of metaloprotinase (MMP 3) the key pathologic events for pannus formation are regulated by IL-9 and its recptor. Thus the IL-9/IL-9R system is a new contributing factor in the cytokine network of PsA and RA.